2005
DOI: 10.1086/429343
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Azithromycin, Alone and in Combination with Chloroquine, for the Treatment of Acute UncomplicatedPlasmodium falciparumMalaria in India

Abstract: Resolution of parasitemia was inadequate with monotherapy with either azithromycin or chloroquine, but combination therapy provided substantially improved clinical and parasitologic outcomes. The combination of azithromycin and chloroquine may be an effective alternative treatment for falciparum malaria and deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 16 publications
3
96
0
Order By: Relevance
“…This study, with the aim of detecting and characterizing PfCRT haplotype distribution, was conducted from September 2004 to July 2006 as part of a series of double-blind, randomized clinical trials which investigated the efficacy of CQ plus azithromycin combination therapy in the treatment of P. falciparum infections in Uganda (Kampala and Kakira), Suriname, and India (states of Goa, Maharasthtra, Madhya Pradesh, Orissa, and Assam) (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study, with the aim of detecting and characterizing PfCRT haplotype distribution, was conducted from September 2004 to July 2006 as part of a series of double-blind, randomized clinical trials which investigated the efficacy of CQ plus azithromycin combination therapy in the treatment of P. falciparum infections in Uganda (Kampala and Kakira), Suriname, and India (states of Goa, Maharasthtra, Madhya Pradesh, Orissa, and Assam) (10).…”
Section: Methodsmentioning
confidence: 99%
“…Adults of Ͼ18 years of age were enrolled in the study upon meeting eligibility criteria and providing informed consent (10). At each site, the informed consent was translated into the local language.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when animals received azithromycin prophylaxis during sporozoite exposure, lower liver loads and superior protection were observed (Friesen & Matuschewski, 2011). The combination of azithromycin and chloroquine has demonstrated synergistic effect against parasite growth in vitro (Nakornchai & Konthiang, 2006) and has shown substantially improved clinical and parasitological outcomes compared to azithromycin or chloroquine monotherapy in vivo (Dunne et al, 2005). In treatment trials with azithromycin-chloroquine in Africa, this drug combination showed non-inferiority compared to mefloquine (van Eijk & Terlouw, 2011).…”
Section: Innovative Application Of Drug Use In the Fieldmentioning
confidence: 99%
“…In accordance with these findings, increasing the dose and frequency of administration of chloroquine can increase plasma concentrations to levels higher than the IC 50 values of chloroquine-resistant parasites. Similar to the artemisinin derivatives, prospects for long-term chloroquine efficacy will be enhanced if it can be used in combination, such as chloroquine-azithromycin (Dunne et al, 2005). With the right combination therapy, the prospects for a chloroquine comeback are good.…”
Section: Status Of Resistancementioning
confidence: 99%